Book-tax difference and value relevance of taxable income after the adoption of financial reporting standards (FRSS) / Rashinah Binti Hossen and Rohaya Md Noor - Hossen,, Rashinah; Md Noor, Prof. Dr. Rohaya (2012)
Malaysia started to adopt FRSs in the year 2006 to replace the Generally Accepted Accounting Principles (GAAP) and International Accounting Standards (IASs). The Financial Reporting Standards claimed to be better than GAAP and IASs because it could improve the quality of financial reporting, more comprehensive, effective and transparent. Rohaya, Nor’azam and Barjoyai (2009) conducted this study before the adoption of Financial Reporting Standards, therefore this paper attempts to extent the study by examining the impact of Book-Tax Difference and whether the taxable income can be used as another alternative to measure the earnings quality after the adoption of Financial Reporting Standards. The result finds the gap between the reported earnings and taxable income is getting smaller after the adoption of Financial Reporting Standards (FRSs). The result also discovers that after-tax taxable income is significant and positively related to market value of common equity. Thus, this paper provides the evidence that the taxable income can be used as another measurement to indicate the earnings quality and firm’s performance after the adoption of FRSs.